Impact of CO2 cap-and-trade programs on restructured power markets with generation capacity investments. (October 2015) - Rocha, P.; Das, T.K.; Nanduri, V.; Botterud, A.
Highlights: The model is used to assess the impact of CO2 cap-and-trade in electricity markets. The generators' competition in a CO2 allowance market similar to RGGI is modeled. Investment decisions and electricity supply bids of generators are also modeled. The methodology is implemented on a sample power network from northern Illinois. Relationship between CO2 allowance prices and emissions, demand, LMPs are obtained. Abstract: A cap-and-trade program is the most widely discussed policy aimed at achieving CO 2 emissions reductions. Since power plants in the US and other industrialized nations are responsible for a sizable portion of CO 2 emissions, the implementation of a CO 2 cap-and-trade program will have a significant impact on the power generation sector. Assessing this impact is a challenging task, especially in restructured electricity markets. Cap-and-trade programs consider multiple design parameters and attributes as well as the creation of a new market for CO 2 allowances, all of which will affect the capacity investment decisions of generators and the bids that generators submit to the day-ahead and real-time electricity markets. In this paper, we develop a game theoretic model driven methodology to assess the impact of CO 2 cap-and-trade programs in restructured electricity markets. The methodology is implemented on a sample power network created from the electricity market data of northern Illinois in the US. The network is assumed to operate under a CO 2 cap-and-trade program similar to the Regional Greenhouse Gas Initiative (RGGI). The impact of cap-and-trade policy on the equilibrium generation expansion plan and the electricity market operation is examined via variations in prices, CO 2 emissions, demand, and evolution of technology mix in the generation portfolio over a planning horizon.